A systematic review and meta-analysis of urinary incontinence following successful obstetric fistula repair: findings from five countries in sub-Saharan Africa - Gedion Asnake Azeze; Kirubel Eshetu Haile; Natnael Atnafu Gebeyehu; Sintayehu Solomon Kena; Tewodros Getachew Tsegaye; Amanuel Yosef Gebrekidan; Yitateku Alelgn; Gizachew Ambaw Kassie; Yordanos Sisay Asgedom (BMC Women's Health)
Abstract Background Obstetric vesico-vaginal fistula is a known complication that can occur following damage to the bladder wall during prolonged obstructed labor and operative delivery. Urinary incontinence following the repair of obstetric fistula remains a significant health problem and can greatly damage a women’s ability to function confidently. There are approximately two million women suffering from urinary incontinence following obstetric fistula repair, most of whom are primarily in Africa. Objective We aimed to systematically review and conduct meta-analysis on the magnitude of urinary incontinence among women following successful obstetric fistula repair in sub-Saharan African countries. Methods We thoroughly searched online database including Medline, Scopus, Science Direct, Excerpta Medica Database, African Journals Online and Google Scholar for eligible articles from their inception to November 10, 2024. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) 2020 checklist. To generate pooled prevalence of urinary incontinence, we used random-effects model. The presence of publication bias was determined using a funnel plot and Egger’s regression test. Results Out of 1044 articles found following our initial search and after titles and abstracts review, we considered 277 full text articles for inclusion. Lastly, a total of 12 articles from five sub-Saharan African countries comprising 6,104 participants met the inclusion criteria for quantitative meta-analysis. The pooled prevalence of urinary incontinence following obstetric fistula repair was 16.32% (95%CI: 11.80, 20.84; I2 = 96.5%, P < 0.001). Conclusion and implications Overall, our findings show post-fistula repair incontinence remains an important clinical problem. Therefore, we believe that policy planners and researchers of sub-Saharan African nations may use the findings of the current study for evidence based care planning and patient counseling strategy. Registration Registered in PROSPERO under protocol number CRD42023416541.